DESAIN PROTOTYPE ALARM DAN PEMADAN KEBAKARAN OTOMATIS MENGGUNAKAN ARDUINO DENGAN KONTROL JARAK JAUH - Novita Putri Wahyudi; Firman Santoso; Salam Bikwanto (CV. Denasya Smart Publisher, 2025)
Fires have the potential to cause significant material losses and even loss of life. Addressing this issue requires a system that can detect and respond automatically. The purpose of this research is to design and build a prototype automatic fire alarm and extinguishing system using a remote-controlled Arduino. This system functions to activate the alarm and automatically activate the extinguishing mechanism when a fire is detected. Furthermore, the system is equipped with a remote control for real-time monitoring and control of the device. Test results demonstrate that the prototype is capable of providing a fast and effective response, as expected. Therefore, this system is a practical, economical, and easy-to-implement alternative for fire prevention, both in households and small-scale industries.